1993
DOI: 10.1116/1.578669
|View full text |Cite
|
Sign up to set email alerts
|

Reaction pathways for ArF excimer laser assisted tungsten chemical vapor deposition from a WF6–H2 gas mixture

Abstract: Photolytic tungsten chemical vapor deposition by an ArF excimer laser from a WF6/H2/Ar gas mixture is a very complicated process with reactions occurring both in series and in parallel. In this article different reaction pathways were modeled and compared with experimental deposition rate data. The absorption cross section for WF6 was measured to 1.7×10−18 cm2 at the ArF excimer laser wavelength of 193 nm. From a rate equation model, it was concluded that the direct photolytic contribution to the deposition ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…It has previously been shown that the H 2 reduction of the laser-generated subfluorides ͑mostly WF 3 and WF 4 ͒ can be related to the particle formation due to the formation of W-W bonds. 9 On the other hand, the net surface reaction…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that the H 2 reduction of the laser-generated subfluorides ͑mostly WF 3 and WF 4 ͒ can be related to the particle formation due to the formation of W-W bonds. 9 On the other hand, the net surface reaction…”
Section: Resultsmentioning
confidence: 99%
“…4,5 It was shown that for a wide range of parameter sets, the tungsten deposition goes through nanoparticle formation from WF 6 /H 2 /M (MϭAr, Kr, Ne, Xe) gas mixtures irradiated by an ArF excimer laser (ϭ193 nm). [6][7][8][9] This is due to gas phase reactions, since the laser beam is aligned parallel to and just above the substrate surface. For metallization purposes the particle formation is an avoidable effect, on the other hand, this LCVD process may be utilized for nanoparticle-film deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The net chemical reaction for tungsten formation from WF 6 and H 2 precursors is The dominant reaction pathway for particle formation during LCVD of W contains several steps, and most likely (i) the photolytic generation of sub-fluorides (mostly WF 3 and WF 4 ), (ii) formation of W−W bonds between the sub-fluorides, and (iii) further reduction by H 2 are the most important . After the particles are formed, they travel downstream by the gas-flow and are heated by following laser pulses (because the particles are still within the reaction zone).…”
Section: Discussionmentioning
confidence: 99%
“…Photolytic (UV excitation) LCVD is also capable of generating ultrafine powders such as nanoparticles containing both iron and carbon 34 and tungsten nanoparticles. 35,36 An interesting characteristic of nanoparticle generation by LCVD is that the interaction of laser light and particles results in detectable blackbody-like radiation of the hot particles. 37 The experimental set-up for tungsten nanoparticle generation by LCVD consisted of a stainless steel vacuum chamber with a cross section of 12 cm 2 .…”
Section: Laser Assisted Chemical Vapor Depositionmentioning
confidence: 99%